UJI AKTIVITAS ANTIBAKTERI FRAKSI n-HEKSAN KULIT BUAH NAGA MERAH (Hylocereus polyrhizus Britton & Rose) TERHADAP BAKTERI Staphylococcus aureus ATCC 25923 - Sri Amalia; Sri Wahdaningsih; Eka Kartika Untari (Jurnal Fitofarmaka Indonesia, 2014)
Inappropiate antibiotic use was one of the main reason that caused pathogenic microorganism resistance, leads to ineffective treatment. One of those resistance bacteria is Staphylococcus aureus. The research for discovering new antibiotics can help with this issue. The peel of red dragon fruit (Hylocereus polyrhizus) is one of the plants that has antibacterial compounds. The aim of this research is to prove and determine the minimum inhibitory concentration (MIC) value of n-hexane fraction of red dragon fruit’s peel againts Staphylococcus aureus ATCC 25923. The peel was maserated with chloroform, then fractinated by n-hexane. Futhermore, the antibacterial properties of the fraction was tested using Disc Diffusion (Kirby-Bauer) methode with 40, 20 dan 10 mg/mL concentrations. Ampisilin used as control positive. Based on the phytochemical screening of the fraction, the n-hexane fraction of the dragon fruit’s peel contain triterphenoid, steroid and alkaloid. Clear zones produced by 40 mg/mL is 12,80 mm and for 20 mg/mL is 11,17 mm. Wherea concentration 10 mg/mL didn’t show any inhibitory zone. According to this reasearch, the MIC value of the fraction is  20 mg/mL.